Sheep feed during low tide on the Flats - Branch Cultural Historical Association (2006)
At the mouth of The River, the delta is exposed twice a day as the ocean recedes from beyond the causeway. Here a considerable expanse of river islands, knows as the Flats, sit in the heart of the valley. High tide surrounds the outer flats while more inland flats are beyond the reach of the ocean. The Flats rival the Wester Cove as another natural wonderland for hiking, bird watching, fishing, swimming, and photography.